Improving Students' Positive Self-Concept through the P5 Program at SMP N 13 Surakarta - June Maulana Ikhsan; Azis Ilham Saputra; Tri Pujiati Sholikhah; Lisnawati Ruhaena (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
School education is a learning process that aims to develop potential with a planned effort. In developing students' potential, it is necessary to form a positive self-concept of students. This study aims to find out how to increase students' positive self-concept using the independent learning curriculum that focuses on the P5 program. The method used is Focus Group Discussion which is a method used to obtain qualitative research data by gathering a small group of people to discuss a particular topic. The research informants for this research were the learning committee team at SMP Negeri 13 Surakarta, consisting of 8 people. From the results of the FGDs that have been conducted, it can be concluded that the independent learning curriculum can improve students' positive self-concept, especially in the P5 program. Because students will be taught to prepare performances independently and are required to cooperate with one another. On the other hand, the teacher can assess the process of activities according to the theme and accompany them directly. The teacher also directs all students to work according to their respective job desks, so that this P5 activity will be felt as a joint activity. In addition, periodic theme changes are also carried out in the application of P5 so that students do not get bored.